(untitled) (Malaysian Management Journal, 2000)
This paper focuses on perception and management of sexual harassment (SH) at the workplace. The study was carried out in Northern Malaysia among 586 public sector administrators. Results showed that 43% of the total male respondents and 47% of the female respondents have faced some kind of sexual harassment. Findings showed that the internal whistleblowing mechanism is also inadequate, though the respondents are quite confiÂdent with the management in reporting SH cases. Finally, the article outline strategies that could ameliorate the occurrence of SH at the workplace as it is important to the organization and the priceless workers in the organization.